Chromium‐Catalyzed Selective Dimerization/Hydroboration of Allenes to Access Boryl‐Functionalized Skipped (E, Z)‐Dienes. (27th November 2020) - Zhao, Yinsong; Ge, Shaozhong
Abstract: A chromium‐catalyzed dimerization/hydroboration of allenes is developed to access synthetically versatile boryl‐functionalized skipped dienes with a catalyst generated in situ from CrCl2 and a pyridine‐2, 6‐diimine ligand mes PDI. A variety of allenes reacted with pinacolborane (HBpin) to afford the corresponding boryl‐functionalized ( E, Z )‐1, 4‐dienes in high yields and with excellent selectivity. Electron paramagnetic resonance (EPR) spectroscopic studies suggest that this chromium‐catalyzed reaction probably proceeds through a chromium(I) hydride intermediate. Abstract : A chromium‐catalyzed dimerization/hydroboration of allenes is developed to access synthetically versatile boryl‐functionalized skipped dienes with a catalyst generated in situ from CrCl2 and a pyridine‐2, 6‐diimine ligand mes PDI. A variety of allenes reacted with pinacolborane (HBpin) to afford the corresponding boryl‐functionalized ( E, Z )‐1, 4‐dienes in high yields and with excellent selectivity.